Penggunaan Kas Masjid dalam Investasi Usaha: Perspektif Fikih Kontemporer: The Use of Mosque Cash in Business Investment: Perspective of Contemporary Fiqh - Henri Priamukti; Azwar, Azwar; Aqbar, Khaerul; Akbar, Fadhlan (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine the use of mosque cash in business investment in a contemporary fiqh perspective. The type of research used in this research is library research with a normative juridical approach. The results of the research show that in general mosque cash can be used (mubāḥ) in business investment, with several conditions that must be met, including: (1) the main needs of the mosque must have been met first; (2) mosque cash originating from zakat to be invested is derived from zakat whose payment is terminated; (3) mosque cash originating from zakat, waqf, infaq and alms, must be invested in businesses that do not violate the Shari'a; (4) mosque cash should be invested in business fields that are believed to be profitable on the basis of a feasibility study, fostered by competent parties, carried out by professional and trustworthy institutions, obtaining permits, there are no poor people who are starving due to investment In this case, the time must be limited, invested in a business that is lawful and with controllable risks.